Diagram Unified Modelling Language (UML) untuk Perancangan Sistem Informasi Manajemen Penelitian dan Pengabdian Masyarakat (SIMLITABMAS) - Siska Narulita; Ahmad Nugroho; M. Zakki Abdillah (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
The management of data collection of research activities, community service, and publications that occur at the National University of Karangturi Semarang is still done manually using Microsoft Excel, which still has various problems related to collecting, storing, searching, processing, and presenting data when needed for the accreditation process. Based on these problems, an information system is needed that can accommodate all the problems experienced by users. Therefore, an information system will be developed to manage all data related to research activities, community service, and publications carried out by lecturers and improve the efficiency of data management. System design is one of the stages of developing an information system. Simlitabmas design has two main objectives, namely to fulfill the needs of users and to provide a clear picture to all personnel involved in system development. System design is one of the important steps in a system development in which a visual representation of a series of processes or activities in an institution or organization is made. One of the modeling or design tools that can be used is the Unified Modeling Language (UML). UML helps describe and design systems, especially in object-oriented programming. In this research, UML diagrams made consist of use case diagrams, activity diagrams, and sequence diagrams.